Noise pollution in wooden furniture industry / Aishah Md Yunos and Suhaimi Muhamed - Md Yunos, Aishah; Muhamed, Suhaimi (2012)
A study was carried out to evaluate the noise exposure among workers in the wooden furniture industry in the Selangor. A total of 8 factories were selected from each city for the study. Portable noise-level measurements showed that the rough-milling operations recorded the highest noise-level in the furniture factories. Noise can be defined as unwanted sound which is very loud irritating to out ears. The workers in wooden furniture are working in the noisy area. Hence, workers in the factories must be provided with hearing protection. They are working without using hearing protection whether their employer are provide it or not. So that, because of that the noise effect on their daily health. This study also revealed that despite the existent of occupational health and safety regulations in Malaysia, its implementation and enforcement within the wooden furniture industry must be improved to ensure the workers safety and health.